Experimental observation of tool wear, cutting forces and chip morphology in face milling ofcobalt based super-alloy with physical vapour deposition coated and uncoated tool - KENTLİ, AYKUT (ELSEVIER SCI LTD, 2007)
Cobalt base superalloys are used extensively in applications requiring good wear, corrosion and heat resistance. The main goal of this study is to examine the effect of machining conditions (cutting speed, feed rate and depth of cut) on tool wear, chip morphology and cutting forces in symmetric face milling of cobalt base superalloy with physical vapour deposition coated and uncoated inserts. with the aim of achieving to achieve this goal, 90 milling experiments were carried out with different cutting speeds, feed rate and depth of cut under dry cutting conditions. The settings of machining parameters were determined by using general full factorial design method. Chip morphology, cutting forces and tool wear were compared by using PVD coated and uncoated hard metal inserts which are obtained dependent on feed rate, cutting speed and cutting depth. The cutting forces increase as the feed rate and depth of the cut increases, but cutting speeds' effect on cutting forces has not been observed for symmetric face milling. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: face milling; cutting forces; tool wear; cobalt base superalloy; chip morphology; MICROSTRUCTURE; LIFE